Physiological ecology of photosynthesis in Prasiola stipitata (Trebouxiophyceae) from the Bay of Fundy, Canada. Issue 3 (21st May 2013) - Kang, Eun Ju; Scrosati, Ricardo A.; Garbary, David J.
Summary: The physiological ecology of Prasiola stipitata was examined in situ from two supralittoral sites in the Bay of Fundy (Nova Scotian, Canada) during November 2011, when the population was undergoing major expansion. Photosynthetic parameters (effective quantum yield, ΦPSII, maximum quantum yield, F v / F m, and relative electron transport rate, rETR) were evaluated using chlorophyll fluorescence of PSII. A largely shaded and continuously moist population showed no change in ΦPSII from one hour after sunrise to sunset in which natural irradiance varied between 3 and 300 μmol photons m −2 s −1 . High irradiance (up to 1800 μmol photons m −2 s −1 ) had no apparent negative impacts on either quantum yield or rETR, but high desiccation in the field reduced quantum yield to almost zero. When thalli were brought into the laboratory, no change in F v / F m was observed up to 60% dehydration; however, there was a steep decline in F v / F m between 60% and 85% dehydration. Thalli showed complete recovery of F v / F m within one hour of reimmersion in seawater after 2 days of desiccation. After 15 days of desiccation full recovery required 24 h and after 30 days of desiccation thalli showed only partial recovery. These observations confirm the adaptation to photosynthesis in high irradiances and the rapid recovery following extreme desiccation observed in other Prasiola species.